LINGUISTIC AND EXTRALINGUISTIC ASPECTS OF STUDYING ENGLISH ANTHROPONYMS IN ACADEMIC DISCOURSE - Katermina, Veronika; Solovyeva, Natalia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The article is devoted to the linguistic and extralinguistic factors while teaching anthroponyms in academic discourse. Being an important element of language and culture they play a crucial role in the process of mastering a foreign language, i.e. contain information about the national and cultural features of a particular ethnic group. Academic discourse refers to the ways of thinking and use of the language in special communicative situations. Its significance lies in the fact that complex social activities like educating students, demonstrating learning, disseminating ideas and constructing knowledge, rely on language to accomplish.Teaching a foreign language is considered in the educational process not only as an instrument of communication and cognition, but also as a way by which a student penetrates the cultural field and mentality of a particular nation. Knowing someone else’s culture and mentality is valuable in two ways. On the one hand, it is associated with the enrichment of the picture of the world, the formation of a dialogical attitude to the phenomena of a different way of life, a different way of consciousness, a different hierarchy of values. On the other hand, one who knows a foreign culture comprehends his own better and deeper, more aware of himself as its bearer.